2007
DOI: 10.1080/10934520701629716
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cadmium in combination with zinc and selenium on ovarian structure in Japanese quails

Abstract: In this study the effect of cadmium, cadmium+selenium and cadmium+zinc administration on the ovarian structure in Japanese quails was studied. The morphometric analysis of the relative volume of primary follicles detected the highest value in control group with a similar value in the group with administration of cadmium with selenium. Lower relative volume is reported in group with cadmium and zinc administration and the group with simple cadmium administration (P < 0.05). The relative volume of growing follic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 27 publications
1
19
0
1
Order By: Relevance
“…The accumulation of Cd in the tissues were as follows: kidney > liver > testis > small intestine. Several authors reported that the organ of higher accumulation of Cd is kidney and also it is a detoxifying organ (Nad et al, 2005;Linde et al, 2004 andMassanyi et al, 2003). In our study also revealed high accumulation of Cd was observed in 30d Cd treated rat kidney (31.578±0.499 µg/g) and low level of Cd concentration was observed in small intestine Table 1.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…The accumulation of Cd in the tissues were as follows: kidney > liver > testis > small intestine. Several authors reported that the organ of higher accumulation of Cd is kidney and also it is a detoxifying organ (Nad et al, 2005;Linde et al, 2004 andMassanyi et al, 2003). In our study also revealed high accumulation of Cd was observed in 30d Cd treated rat kidney (31.578±0.499 µg/g) and low level of Cd concentration was observed in small intestine Table 1.…”
Section: Resultssupporting
confidence: 59%
“…Several essential trace elements like Selenium (Se), Copper (Cu), Zinc (Zn) and Iron (Fe) participate in controlling various metabolic and signaling pathways. In vitro studies suggests there is competition for transport mechanism between Cd and some essential trace elements like Zn and Cu (Hakan et al, 2001), Se (Hijova and Nistiar, 2005) and Fe (Rodriguez-Matas et al, 1998) in rats and Zn and Se in Japanese quails (Nad et al, 2005) and calcium in suckling rats (Saric et al, 2002). Se is involved in the metabolism of glutathione (GSH) which is related to reduce toxicity of chemical carcinogen and several heavy metals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of atretic follicles was significantly higher after Cd administration. In the other study, massanyi et al prove the negative effect of Cd on the ovarian structure [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Basic histological studies showed that in the ovary cadmium causes a decrease in the number of primary follicles. Massanyi et al in their research showed that the number of atretic follicles was significantly higher in all groups administered cadmium and the diameter of the follicles was significanlty smaller in the primary follicles of group C compared with control group [4], [5]. The mechanism cadmium damage the ovarium might through the formation of advance glycation end products (AGEs) by nonenzymatic reaction and the formation of advance oxidation protein products (AOPP) [6].…”
mentioning
confidence: 99%